2014
DOI: 10.1111/jcms.12183
|View full text |Cite
|
Sign up to set email alerts
|

The Economy Strikes Back: Support for the EU during the Great Recession

Abstract: This article looks at the role of economic conditions in shaping people's attitudes to the EU during the Great Recession. In contrast with previous research, findings suggest that in this particular instance support for the EU across Member States was affected by economic factors. In particular, both higher unemployment and higher interest rates were strongly associated with lower levels of support. Findings also suggest that young Europeans responded more strongly to adverse economic conditions during the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…The result of those was a clearly visible convergence of opinions on the EU across the regions. This finding corroborates the insights from previous studies which pointed to the economic crisis engulfing Europe since 2008 as the main factor behind the growing euroscepticism and disenchantment with the EU (e.g., Braun & Tausendpfund, ; Gomez, ). Our regional level analysis, however, offers a more nuanced view by showing that the erosion of positive EU image was particularly strong in regions where previously positive opinions on the EU predominated prior the crisis.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The result of those was a clearly visible convergence of opinions on the EU across the regions. This finding corroborates the insights from previous studies which pointed to the economic crisis engulfing Europe since 2008 as the main factor behind the growing euroscepticism and disenchantment with the EU (e.g., Braun & Tausendpfund, ; Gomez, ). Our regional level analysis, however, offers a more nuanced view by showing that the erosion of positive EU image was particularly strong in regions where previously positive opinions on the EU predominated prior the crisis.…”
Section: Resultssupporting
confidence: 92%
“…How did the crisis affect the citizens' support for the EU? While some studies other impacts of the global crisis on EU support suggested that national identity and political institutions remain key determinants of the surging Euroscepticism (Serricchio, Tsakatika, & Quaglia, ), more recent research has shown that negative economic effects of the crisis in the EU, and especially the surging unemployment, have indeed negatively impacted upon the levels of support for the EU, particularly among younger citizens (Gomez, ). The decline in EU support was more related to the Euro crisis, rather than the global economic slowdown, and thus thisrelationship was more pronounced in the Eurozone countries (Braun & Tausendpfund, ).…”
Section: Introductionmentioning
confidence: 99%
“…This, on the one hand, echoes the claims that the (declining) economic outlook has negative effects on the citizens' perceptions of the EU (Braun & Tausendpfund, 2014;Gomez, 2015). On the other hand, it indicates that there may be a problem with the effectiveness of communication of the results of Cohesion Policy interventions and points to the need to address that problem by European, national and regional policy-makers.…”
Section: Resultsmentioning
confidence: 66%
“…Numerous studies have argued that support for European integration derives from the ability of EU institutions to deliver the economic goods, either for individual households, or for the nation as a whole (Christin, ; Gabel, ; Gomez, ). While earlier studies find mixed results with respect to the impact of economic indicators on attitudes towards the EU before the crisis, Gomez () shows that EU support is indeed correlated with macroeconomic conditions post‐crisis , which is unsurprising given the unpopularity of EU‐backed austerity measures in some crisis countries. On the other hand, Armingeon and Ceka () argue that attitudes towards the EU are primarily derivative of public opinion about national‐level politics and policy.…”
Section: Hypothesesmentioning
confidence: 99%